Variability Studies in Lagerstroemia (Lagerstroemia speciosa Pers.) - Jamaludheen, V.; Gopikumar, K.; Sudhakara, K. (Indian Forester, 1995)
The present study was undertaken in the College of Forestry, Vellanikkara with a view to study the extent of variation in various morphological characters among selected seedling population of Lagerstroemia speciosa. An attempt was also made to find out correlation if any. That existed between various tree growth parameters. In the present study considerable variation was observed in the vigour of trees expressed as various vegetative, flowering, fruit and seed characters. The study emphasises the fact that open pollinated seeds, even from the selected mother trees for seed purposes win not result in progenies behaving uniformly. Vegetative propagation is perhaps the only assurance for the transmission of characters uniformly from mother trees to their progenies.